If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9b + -22 = 7b + -16 Reorder the terms: -22 + 9b = 7b + -16 Reorder the terms: -22 + 9b = -16 + 7b Solving -22 + 9b = -16 + 7b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7b' to each side of the equation. -22 + 9b + -7b = -16 + 7b + -7b Combine like terms: 9b + -7b = 2b -22 + 2b = -16 + 7b + -7b Combine like terms: 7b + -7b = 0 -22 + 2b = -16 + 0 -22 + 2b = -16 Add '22' to each side of the equation. -22 + 22 + 2b = -16 + 22 Combine like terms: -22 + 22 = 0 0 + 2b = -16 + 22 2b = -16 + 22 Combine like terms: -16 + 22 = 6 2b = 6 Divide each side by '2'. b = 3 Simplifying b = 3
| -2(1-6r)=-2+4r | | 4v+6=41-3v | | 4s+14=2s+66 | | 3x^2+6x=168 | | p+p+64=180 | | -3(x-1)=-2x-3 | | 2a-21=a | | 12x-11y=23 | | 3/13=u/10 | | 5(2x+5)-1=-2x | | 2b-48+2b-96=180 | | 3u-64=u | | 10y+9=13y+3 | | 3n+4(5n+2)=8+3n | | 16z-21+2z+39=180 | | -3(1-5m)+4=1-2m | | 7=an-1+-15 | | 4c-65=5c-85 | | 4c-65=5c-68 | | -2+3p=6p-4-2p | | 7y+73=4y+94 | | -5+6m=5m-8 | | t=2t-51 | | 3y=-x-2 | | 4y-5x=4y-5x | | 8/9-5/6×1/3 | | 4b+64=2b+68 | | 8n-n=-4+6n | | 7c-77=4c-35 | | -4x+4=11+2x-7x | | 9x+16y=7 | | 2/y-3=3/y |